Development of Learning Media Using Genially to Increase Student Learning Interest at Smk Muhammadiyah 2 Kuningan in Basic Graphic Design Subjects - Irpan, Muhammad; Lutfi, Ahmad Fajri (Journal of Social Science, 2024)
Muhammad Irpan (201223025). Development of Learning Media Using Genially to Increase Student Interest in Learning at SMK Muhammadiyah 2 Kuningan in Basic Graphic Design Subjects. The background to this thesis is that students' interest in learning at SMK Muhammadiyah 2 Kuningan in the Basic Graphic Design subject is still relatively low. This is caused by learning methods that are less interesting and interactive. Genially is an online platform that allows the creation of interesting and interactive learning media. The aim of this thesis is to develop learning media using Genially to increase students' interest in learning in the Basic Graphic Design subject. The main problem in this research is "Can learning media developed using Genially increase students' interest in learning in Basic Graphic Design subjects?". This research uses the Research and Development (R&D) method. The development model used is the development of Borg & Gall's instructional learning media (Puslitjaknov, 2008; Utomo, 2015) which is simplified into 5 main steps, namely: analyzing the product to be developed, developing the initial product, expert validation and revision, conducting field trials small scale, large scale field trials. The learning media developed was tested on students in class X TKJ and X RPL at SMK Muhammadiyah 2 Kuningan. Based on the results of this research analysis using a paired samples test with a significance value (2-tailed) of 0.000 <0.05, it shows that there is a significant difference between the initial variable (pretest) and the final variable (posttest), so that this Genially learning media can be used as a learning media primarily by students.